Qualidade do abacate 'HASS' frigoarmazenado submetido a atmosferas modificadas ativas - Vieites, Rogério Lopes [UNESP]; Russo, Viviane Citadini; Daiuto, Érica Regina [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The objective of this study was to evaluated conservation of 'Hass'avocado submitted to the application of active modified atmosphere during cold storage. The fruits were packed in polyethylene+nylon and injected with mixture of gases constituting the treatments: I - the environment gas mixture (21.0 kPa of O2+0.03 kPa of CO2); II - 4.0 kPa of O2+5.0 kPa of CO2 ; III - 4.0 kPa of O2+6.0 kPa of CO2 ; IV - 4.0 kPa of O2+7.0 kPa of CO2 and V - 4.0 kPa of O2+8.0 kPa of CO2). The packing containing the fruits were stored in cold chamber at a temperature of 10±1ºC and relative humidity of 90±5%, for 25 days, with analyses performed every 5 days. The parameters evaluated were weight loss, respiratory activity, hydrogen potential (pH), firmness, titrable acidity (TA), soluble solids (SS), and activity of pectinmethylesterase (PME) and polygalacturonase (PG). Fruits submitted to the concentration of 4.0 kPa of O2+ 7.0 kPa showed the best quality mainly with less mass loss and low production of CO2.

O objetivo deste trabalho foi avaliar a conservação do abacate 'Hass'frigoarmazenado submetido a atmosferas modificadas ativas. Os frutos foram acondicionados em embalagem de náilon+polietileno e submetidos à injeção de mistura de gases, constituindo os tratamentos: I - mistura gasosa do ambiente (21,0 kPa de O2+0,03 kPa de CO2); II - 4,0 kPa de O2+5,0kPa de CO2 ; III - 4,0 kPa de O2+6,0 kPa de CO2 ; IV - 4,0 kPa de O2+7,0 kPa de CO2, e V- 4,0 kPa de O2+8,0 kPa de CO2). As embalagens contendo os frutos foram armazenadas em câmara frigorífica, a uma temperatura de 10±1ºC e umidade relativa de 90±5%, durante 25 dias, sendo as análises realizadas a cada 5 dias. As análises realizadas foram perda de massa, atividade respiratória, potencial hidrogeniônico (pH), firmeza, acidez titulável (AT), sólidos solúveis (SS) e atividade das enzimas pectinametilesterase (PME) e poligalacturonase (PG). O tratamento em que os frutos foram submetidos à pressão parcial de 4,0 kPa de O2+7,0 kPa de CO2 foi o mais efetivo na conservação dos frutos, principalmente pela menor perda de massa e baixa produção de CO2.
Avocado 'HASS' quality subjected to modified atmospheres and cold storage
Keywords: Persea americana Mill; postharvest; packing; Persea americana Mill; pós-colheita; embalagem